Design of an Ultra-Wideband Two-Element MIMO Antenna with Improved Performance (International Journal of Communication Systems and Network Technologies, 2025)
In this paper an efficient two element ultra wideband MIMO antenna  is designed. First single UWB is designed. Then two element MIMO antenna  is designed and its characteristics are observed. Then using double couplet defected ground structure the antenna performance is improved interms of isolation, ECC, DG. The designed 2 element MIMO antenna  with DGS operates over (2.09-12.01)GHz. Due to DGS the mutual copuling has reduced by 13.61dB and return loss improved by 10.1dB at X-band frequency. ECC close to zero and diversity gain nearly 10 are achieved for the MIMO antenna with DGS. The simulations are carried using HFSS software and simulation results are compared with measured results.
Keywords: Defected Ground Structure(DGS); Ultra-Wideband(UWB); Envelope Correlation Coefficient(ECC); Diversity Gain(DG) And MIMO Antenna